INTERNET GAMING DISORDER IN STUDENTS OF PESHAWAR: A CROSS SECTIONAL SURVEY - Salam, Zahwa; Sadiq, Zainab; Tajamul, Urooj; Sethi, Mifrah Rauf; Irfan, Muhammad (Journal of Ayub Medical College Abbottabad, 2019)
Background: Internet gaming, though getting popular, is becoming a risk to physical and psychological health, especially in adolescents, as it contributes to sedentary lifestyle. To gauge the extent of the problem in our setup, we decided to find the frequency of internet gaming disorder in students of Peshawar and identify their motives for playing these games. Methods: This Cross-sectional survey was conducted from February to December 2018 and included students of Private and Public institutes of Peshawar. They were invited to complete a questionnaire comprising of Internet Gaming Disorder Scale-Short Form (IGDS-SF9), which includes 9 questions, with some additional demographic questions. The data were analysed using SPSS v.25. Results: The mean age of the sample (n=2116) was 21.5±2.1 years with the age range of 16-28 years. The cronbach’s alpha reliability of IGDS-SF9 in our study was 0.805. Majority of the participants were males (n=1261, 59.6%) and were from Private sector institutes (n=1314, 62.1%). A total of 32 (1.5%) students reported having Internet Gaming disorder. The results of chi square test showed that significantly more male students played games for social motives (p=.032), whereas significantly more female students played games for coping motives (p=.001). Pearson correlation results showed a significant positive correlation between time spent on gaming and internet gaming disorder (p=.000) and between internet gaming disorder with recreation as a motive (p=.027). Conclusion: Internet Gaming is getting common in our setup and IGDS-SF9 can be effectively used in our population because of its reliability. Keywords: Internet Gaming Disorder, Students, Peshawar